Experiment study evaluating parameters effects on the vibration of rotor - Tran , Thanh Lam; Dang , Thiện Ngôn; Tran , Thái Sơn; Le , Chí Cương (Journal of Technical Education Science, 2021)
Vibration in the rotary shaft is a common phenomenon observed in rotor systems. Determining the factors that cause the vibration to implement the vibration reduction measures to ensure the rotor running stably is one of the urgent requirements today. In this paper, a model of rotor vibration assessment has been proposed which allows to investigate the main parameters influencing rotor vibrations including critical speed, unbalance eccentricity and initial phase angle. The experimental results show that: when the speed is near the critical speed, the vibration becomes unstable and the amplitude of the oscillation increases sharply; the amount of unbalance increases leading to an increase in amplitude of oscillation; the initial phase angle of the load position, if changed during operation, will make different oscillation periods leading to an increase or decrease in bending stress leading to rotor fatigue.